UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS IV UPTD SD NEGERI 6 PEUSANGAN PADA MATERI BAGIAN-BAGIAN TUMBUHAN MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Nanda Khaira; M. Rezeki Muamar; Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was based on the low student learning outcomes caused by the less effective learning process. Learning activities tended to be boring due to the teacher’s limited mastery of innovative learning models and the lack of variety in the instructional media used. This study aimed to improve the learning outcomes, teacher and student activities, and student responses of fourth-grade students at UPTD SD Negeri 6 Peusangan on the topic of parts of plants through the implementation of the Contextual Teaching and Learning (CTL) model. This study used a qualitative approach with the type of Classroom Action Research (CAR), which was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included tests, observations, and questionnaires. The data were analyzed descriptively using qualitative and quantitative methods through percentages of learning mastery, teacher and student activities, and student responses. The results showed that the implementation of the CTL model was able to improve student learning outcomes. Learning mastery increased from 66.67% in Cycle I to 94.4% in Cycle II. Teacher activities also improved from the sufficient category (63.5%) to the very good category (94.7%), while student activities increased from the low category (55.3%) to the very good category (92.9%). In addition, student responses toward CTL learning showed a very good category with an average percentage of 86.67%. Therefore, it can be concluded that the Contextual Teaching and Learning (CTL) model is effective in improving learning outcomes, activities, and student responses on the topic of parts of plants in Grade IV of UPTD SD Negeri 6 Peusangan. Keywords: Contextual Teaching and Learning (CTL), learning outcomes, parts of plants.